(untitled) (Research, Society and Development, 2021)
The article aims to highlight that during the COVID-19 pandemic, active methodologies were the means provided to students by educational public policies in order to lead them to be protagonists of their teaching and learning process, through alternatives for consolidation of your learning without needing the physical presence of the teacher. Faced with the new reality of Brazilian education, teachers had to adapt to new technologies in order to sanction the demands imposed by educational institutions to provide students with quality education, without losing their school earnings imposed by the new educational reality. In ancient times, distance education was not seen as a quality education, and suddenly the world needed online education to bring knowledge to thousands of children and young people during the pandemic period. Educational institutions had to adapt to the new technological reality to make up for the absence of in-person classes, without losing the quality of teaching. It is noteworthy that any new proposal for the evolution of education requires studies and training of those involved in the teaching and learning process, where teaching intuitions promote ways for teachers and students to obtain training to handle new technologies in favor of learning. Given the above, online education came to meet the demands of education systems so that students need to be the protagonists in the construction of their learning with the computer and cell phones as their main study tools.